Legitimising the Status Quo through the writing of Biography: Ngwabi Bhebe's Simon Vengayi Muzenda & the Struggle for and Liberation of Zimbabwe - Mhiripiri, Nhamo A. (2016)
Simon Vengayi Muzenda & the Struggle for and Liberation of Zimbabwe (2004) is a biography written by historian Ngwabi Bhebe in honour of illustrious Zimbabwean nationalist and politician, the late Vice President Simon Muzenda. The book calls for debate on the way it was constructed and its assumptions about the writing of biography and the larger questions concerning national identity and unity. Human society is differentiated along various variables such as social classes, ethnic and racial groups, gender, age and even geographical environment. Individuals and social groups hence are heterogeneous due to these variables. The individuals and social groups have differing, often conflicting, needs and interests and occupy different and at times dissimilar positions of socioeconomic and political power and status. These groups have values, opinions and attitudes towards other individuals, groups and the world that they articulate or express in literature and the media. These expressions can reveal different types of individual and group differences. Due to these differences, each act of expression by an individual or group, or each act of writing, is a potential site of struggle because there are competing needs and interests, as well as competing systems of values and work meant to justify the needs and values.